Gamification in Project Management - Mahu Raluca Petronela (Studies in Business and Economics)
Studies have continuously shown that motivation is a key factor in the process of pursuing success. Domains such as education and business highly rely on intrinsic and extrinsic motivation to drive personal and professional performance, foster innovation and achieve the proposed goals. Studies also highlight a decrease in motivation levels across various fields of activity. Considering this, individuals and companies have been searching for solutions to increase motivation and engagement. A less popular one is gamification. My study focuses on the impact of gamification on project management. Keeping a team motivated is an important responsibility for leaders. Moreover, individual and collective well-being can have a significant impact on performance and general satisfaction in a project. In light of this, I explored the effects of implementing points, leaderboards, badges and peer-to-peer collaboration, as gamification elements, on the performance and general satisfaction of a project team at Amazon Iași. By conducting both a qualitative and quantitative analysis, the study aimed to identify the possibility of perceiving gamification as a solution for increasing team motivation and performance. My findings show that most members of the team felt more satisfied after interacting with gamification, but their performance KPIs did not reveal any obvious change. This underscores the need to expand the research within the field of project management and gamification.